The Largest European Blackberry Producer: A Research Case Study on Entrepreneurship and Family Business - Ajay A Chauhan; Alfonso Vargas-Sánchez; María Moral-Moral (International Journal of Family Business Practices, 2018)
The present paper is based on a field research on the evolution of a saga of family entrepreneurs in Spain, with four generations involved. From the modest beginnings of a canned tomato factory, longer than a century ago, the case explains its transformation up to the current reality of being recognized as the largest blackberry European producer, named ‘Agrícola El Bosque’. Through the personal experience of its main characters, the case displays the very different stages through which this entrepreneurial family has traveled, especially the keys to the successful development of ‘Agrícola El Bosque’, including the last major project that has promoted, based on a process of cooperation with other berries producers in the area. This commercial alliance, branded as 'Plus Berries', leads us to reflect on the future of the growth model followed until now by this family business. On the foundations of this case, some lessons can be extracted and shed light on particular aspects of the scientific literature on family business management, as well as on how entrepreneurial spirit can be fed and flourish at the heat of the development and consolidation of a cluster of companies in an industry.